Heavy-light four-quark states in the charmonium region in a Bethe-Salpeter and Dyson-Schwinger approach - Wallbott, Paul C.; Justus Liebig University Giessen (My University, 2019)
In this thesis we present the first calculation of heavy-light four-quark states in the Bethe-Salpeter and Dyson-Schwinger approach. Furthermore, we describe the lightest scalar quark-antiquark state as a dynamical resonance within the same framework.
Keywords: ddc:530